Assessment of Renal Perfusion in Transplanted Kidney Patients Using Pseudo-Continuous Arterial Spin Labeling with Multiple Post-Labeling Delays. Issue 130 (September 2020) - Ahn, Hyun-Seo; Yu, Hee Chul; Kwak, Hyo Sung; Park, Sung-Hong
Highlights: Renal perfusion for patients within a week after renal transplantation was measured. Registration and background suppression reduced perfusion signal variations. Transplanted kidneys showed higher RBF than those of normal subjects. Abstract: Purpose: To investigate technical issues for implementing pseudo-continuous arterial spin labeling (pCASL) for renal perfusion measurements in transplanted kidney patients (TK) in the early postoperative recovery phase. Methods: Eleven subjects were scanned: TK (N = 4, 42 ± 8.1Y) and normal volunteers (NV) (N = 7, 25 ± 3Y). In 3.0 T clinical MRI, pCASL with a 2D balanced steady-state free precession readout was applied with four different post-labeling delays: 0.5/1.0/1.5/2.0 s. Perfusion images were acquired with and without background suppression and processed with and without registration for comparison. Renal blood flow (RBF) and arterial transit time (ATT) values were calculated from each pixel of images. The F-test, Wilcoxon signed-rank test, and Wilcoxon rank-sum test were used for statistical analyses. Results: Background suppression decreased signal variations for both NV and TK. Registration suppressed effects of kidney motion for NV, which was not critical for TK. The renal cortex showed greater perfusion than the renal medulla in both NV and TK(p < 0.01). TK showed greater renal perfusion than NV(p < 0.05). Cortical and medullary RBF values were 271.8 ± 43.5, 119.1 ± 15.1 ml/100 g/min for NV and 358.3 ± 36.4, 141.0 ± 11.5 ml/100 g/min for TK. TK showed longer ATT values than NV(p < 0.01). ATT values in the cortex and medulla were 641 ± 141 and 746 ± 150 ms for NV and 919 ± 49 and 935 ± 81 ms for TK. Conclusions: We demonstrated that although there is no discernible motion of the transplanted kidney, background suppression is necessary to suppress signal fluctuations in renal perfusion measurements. Also, relatively high RBF and long ATT values were observed in the transplanted kidneys in the early postoperative recovery phase, which requires further longitudinal studies.